IMF Survey, Volume 31, Issue 04. (IMF Survey; IMF Survey ;, 2002)
The Group of Seven Finance Ministers and Central Bank Governors met in Canada on February 8-9 to discuss the global economy, the importance of fostering development, and ongoing efforts to combat the financing of terrorism. The Managing Director of the IMF participated in the meeting.